2020
DOI: 10.1038/s41598-020-74951-8
|View full text |Cite
|
Sign up to set email alerts
|

Herding in human groups is related to high autistic traits

Abstract: Herding is ubiquitous throughout all social life forms, providing beneficial outcomes. Here, we examine whether herding emerges spontaneously in human groups and whether it adheres to the core principles of herding observed in the animal kingdom. Using a computerized paradigm involving the movements of circles, we tested the emergence of spontaneous and intentional herding of 136 participants assigned into groups of four participants. Herding was assessed by measuring directional synchrony in the movements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 102 publications
(127 reference statements)
0
22
0
Order By: Relevance
“…Additionally, a recent study showed that individuals with high autistic traits tend to display a reduced spontaneous synchrony in human groups compared to individuals with low autistic traits. However, this tendency is recovered when synchrony is intentional [25]. Finally, adults with ASD exhibit a reduced ability in their modification of grasping movements in a task that required a synchrony of their movements with their respective partners [26].…”
Section: Aberrant Interactional Synchrony Of People With Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study showed that individuals with high autistic traits tend to display a reduced spontaneous synchrony in human groups compared to individuals with low autistic traits. However, this tendency is recovered when synchrony is intentional [25]. Finally, adults with ASD exhibit a reduced ability in their modification of grasping movements in a task that required a synchrony of their movements with their respective partners [26].…”
Section: Aberrant Interactional Synchrony Of People With Autismmentioning
confidence: 99%
“…Autistic traits are distributed on a continuum ranging from extreme to normal scores, which reflect the variation of the autistic traits across the general population [48]. Thus, similar to numerous studies [25,[49][50][51], the current study focused on individuals who are not diagnosed with ASD, but who vary in their possession of autistic traits.…”
Section: Is There a Link Between Motor Abnormalities And Aberrant Interactional Synchrony In Asd?mentioning
confidence: 99%
“…To measure real-time synchronization among interacting participants, the study used a computer-based movement synchronization multi-agent paradigm (Marton-Alper et al, 2020). This game allows individuals to interact nonverbally by controlling the movement of circle-shaped figures with different colors.…”
Section: Methodsmentioning
confidence: 99%
“…3) Sync conditionthis condition is similar to the free condition, however the participants are instructed to synchronize their movement to the best of their ability. The order of the conditions was maintained for all participants as was established in a previous study (Marton-Alper et al, 2020) so that instructed synchrony will not affect the emergence of spontaneous synchrony right after it.…”
Section: Synchronization Taskmentioning
confidence: 99%
See 1 more Smart Citation